Impacts of land use change on soil erosion in a Himalayan watershed: Implications for sustainable watershed management - Gurung Pathak, Shreejana; Kafle, Gandhiv; Pathak, Hem Kumar (Journal of Agriculture and Natural Resources, 2025)
Soil erosion is a major environmental challenge in Nepal’s Middle Hills, threatening agricultural productivity and watershed sustainability. This study aims to quantify long-term land use/land cover (LULC) changes and assess spatial patterns of soil erosion risk in the Karra River watershed, Makawanpur District, over a 20-year period. Multi-temporal Landsat imagery from 2003, 2013, and 2023 was used to analyse LULC dynamics, while soil erosion was estimated using the Revised Universal Soil Loss Equation (RUSLE) integrated with Geographic Information Systems (GIS) and remote sensing. The RUSLE model incorporated rainfall erosivity, soil erodibility, slope length and steepness, cover management, and conservation practice factors. The watershed was further subdivided into 29 sub-watersheds to prioritize areas for conservation intervention. The results reveal substantial LULC changes between 2003 and 2023, including a 357.1% expansion of built-up areas, a 6.1% increase in forest cover, and a 10.2% decline in cropland. Estimated annual soil loss ranged from <5 to 463 t/ha/yr, with a watershed-wide mean of 8.32 t/ha/yr. Approximately 66.9% of the watershed experienced low erosion (<5 t/ha/yr), while 21.87% was classified as high to very severe erosion (>20 t/ha/yr). Sub-watershed prioritization identified SW12 as the most erosion-prone unit, with an average soil loss of 40.2 t/ha/yr. Areas experiencing rapid urban expansion and agricultural land conversion exhibited localized but elevated erosion risks. The study concludes that integrating LULC change analysis with RUSLE-based modelling provides a spatially explicit framework for identifying erosion hotspots and supporting targeted soil and water conservation planning in data-scarce mountainous regions.